Impact of modern evolution of Paphos town to its ancient necropoleis. A multi-temporal GIS and earth observation analysis - Lysandrou, Vasiliki; Agapiou, Athos; Hadjimitsis, Diofantos G. (My University, 2015)
Hellenistic and Roman ancient cemeteries are spread all over the territory of the island of Cyprus, consisting one of the major archaeological data sites. Ancient necropoleis due to their tombs "manufacturing" nature, being almost exclusively underground and hewn out of the natural rock, are preserved in a great majority respect to their equivalent domestic and other kinds of architectural remains which are primarily constructed above the ground. Having that in mind, it's understood that their thorough excavation and study could add significantly to recent archaeological research. Unfortunately, being usually neglected and mainly due to lack of economic resources, no planned excavation of tombs is usually undertaken. On the contrary, most of the tombs are to be found accidentally during infrastructural works or other modern development activities, such as roads, sewage systems and others. This reality of course deprives the archaeologists of a scrupulous study since damages are to be done to the tombs in combination to the tight time schedules that usually pushing towards the fast completion of an archaeological project, not permitting the necessary time for fully understanding in context. In this direction, remote sensing techniques are nowadays an extremely useful tool in the hands of archaeologists, for overlapping the above described modern reality. In the present paper will be briefly addressed the use of remote sensing techniques for monitoring the funerary archaeolandscape of Hellenistic and Roman Cyprus in an effort of sustainable planning, leading to its better preservation.
Keywords: Cyprus; Funerary landscape; GIS; Hellenistic and Roman tombs and cemeteries; Management; Preservation; Remote sensing